Articulação e integração metropolitana, o papel das cidades pequenas na região de Campinas (SP) - Orlando Moreira Jr (Confins)
The intention of this paper is to present research results that aimed to analyze small cities within a metropolitan area. Economic, demographic and spatial aspects help to identify general logic and private logics in this urban and regional dynamics. The paper presents elements that confirm or deny the idea that a small town located next to a large economically dynamic center can provide better social and economic performance.